LITHUANIA-UKRAINE: HISTORICAL CONNECTION AND PRESENT REALITIES - VIZNIAK, Yaroslav (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article states that Lithuanian-Ukrainian relations occupy an important place in the national history of both states and the pan-European historical process. The interstate political relations that shape the general trends of bilateral cooperation are analyzed. The importance of ties between Ukrainian and Lithuanian civil societies in terms of incentives for democratic transformations and the European choice of Ukraine is shown. The acquisition of state independence by Ukraine opened up new opportunities for cooperation with the countries of the world, one of which was the Republic of Lithuania, the tradition of relations with which dates back to the Middle Ages. On the other hand, the presence of commonality in the positions of Ukraine and Lithuania on a wide range of foreign policy issues, primarily security policy, and the issue of vulnerability to Russian political interference contributed to the fairly quick establishment of a dialogue between the two countries. The initial stage of development after the declaration of independence of both states turned out to be similar in many respects, both in domestic and foreign policy. The geopolitical space determined the main parameters of the activities of Ukraine and Lithuania in the international arena. Being in the sphere of interest of the USA, the EU and Russia dictates the need for geopolitical choices for both states. It is clear that this choice is decisive for development prospects. In this context, it is precisely the experience of the Republic of Lithuania that should be taken into account, in which a consensus of political forces regarding the foreign policy orientation of the country was reached almost immediately after the declaration of independence. It was found that the political relations between Ukraine and Lithuania underwent a rapid evolution at their own pace, although the starting moment was not dynamic enough. After the establishment of diplomatic relations, the political relations between the two countries were in a state of a certain political "lull", connected, first of all, with the difficult national political situation in Lithuania and the fascination of its former leadership with the Western vector of foreign policy.